Generation Z: Profile of Psychological Capital in Students - Laili, Januariya; Linsiya, Ria Wiyatfi (Procedia of Social Sciences and Humanities, 2024)
Generation Z is the population that dominates the Indonesian population who are currently entering the world of work or are preparing to enter the world of work. Gen Z has different characteristics, especially lower psychological vulnerability than previous generations. One of the factors that influences individual work behavior is psychological capital. This research aims to obtain an overview of the psychological capital of Gen Z in students who are currently studying at university. The method used was a quantitative approach involving 124 students at Faculty X. The sampling technique used was accidental sampling . The instrument used in this research uses a psychological capital scale with four dimensions, namely hope, optimism, self-efficacy and resilience which Platania and Paolillo have, which consists of 12 question items. The analysis technique used in this research is descriptive analysis with the help of Jamovi . Based on the results of the descriptive test, it is known that the psychological capital of Gen Z students at Faculty X is in the low category. This means that students tend to lack self-confidence, do not have definite goals and how to achieve these goals and in completing assignments and when they experience failure they tend to have difficulty getting back up